2021
DOI: 10.1001/jamanetworkopen.2021.33805
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal History of Spontaneous Abortion and Stillbirth With Risk of Congenital Heart Disease in Offspring of Women With vs Without Type 2 Diabetes

Abstract: IMPORTANCEThe associations of maternal history of spontaneous abortion (SA) and stillbirth with congenital heart disease (CHD) remain elusive. OBJECTIVE To evaluate the associations of maternal history of pregnancy loss with CHD in offspring and the role of maternal type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Evidence regarding VD nutrition and its relationship with all adverse outcomes is controversial. The risk of spontaneous abortion or stillbirth may be associated with multiple complicated factors, including consanguineous marriage [ 70 ], age [ 70 ], BMI [ 71 ], history of chronic disease [ 72 ], passive smoking [ 73 ], and alcohol intake [ 71 ]. Therefore, the benefits of VD supplementation during pregnancy should be evaluated further through rigorous interventional studies.…”
Section: Maternal Vitamin D Status and Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…Evidence regarding VD nutrition and its relationship with all adverse outcomes is controversial. The risk of spontaneous abortion or stillbirth may be associated with multiple complicated factors, including consanguineous marriage [ 70 ], age [ 70 ], BMI [ 71 ], history of chronic disease [ 72 ], passive smoking [ 73 ], and alcohol intake [ 71 ]. Therefore, the benefits of VD supplementation during pregnancy should be evaluated further through rigorous interventional studies.…”
Section: Maternal Vitamin D Status and Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…In 2021, a cohort study of 1,642,534 offspring born in Denmark reported that maternal history of spontaneous abortion were associated with increased risks of overall CHD, and the risk was further enhanced by gestational type 2 diabetes [ 19 ]. A hospital-based study in Southern Israel reported 36% increased risk of CHD after maternal history of recurrent spontaneous abortion (> = 3 times) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to retrospective studies, PGDM was reported to be highly associated with congenital heart diseases (CHDs) ( 52 56 ) and fetal diastolic dysfunction ( 58 ). Even in non-diabetic pregnant women, an elevated glucose level in the first trimester was directly correlated with an increased risk of CHD in the offspring ( 57 ).…”
Section: The Adverse Effects Of Maternal Diabetes On Offspringmentioning
confidence: 99%